Annual Plan 1984-85 Part I-Outline Union Territory of Delhi - Planning Commission (Planning Commission, 1984)
The need and priorities for a fast expanding Metropolis like Delhi are different from those of other States end Union Territories. The plans for Delhi, while they mosh with the broad policy objectives of the national plans, differ in content and strategy owing to the special characteristics and requirements of Delhi.
Planning Department, Delhi Administration